Ribbon Knots of 1-Fusion, the Jones Polynomial, and the Casson-Walker Invariant - Mizuma, Yoko (Revista Matemática Complutense, 2005)
We give an explicit formula for the Casson-Walker invariant of double branched covers of S3 branched along ribbon knots of 1-fusion.